Joint Hybrid/Passive Beamforming Design in IRS-aided Multi-User MISO Systems for PS-SWIPT - Ntougias, Konstantinos; Krikidis, Ioannis (SPAWC : signal processing advances in wireless communications, 2022)
This paper considers an intelligent reflecting surface (IRS)-aided multiple-input single-output broadcasting system for power-splitting (PS) simultaneous wireless information and power transfer, where the access point adopts an analog/digital architecture. We aim at jointly optimizing the hybrid precoder, passive beamformer (PB), and PS ratios, such that the transmit sum-power is minimized subject to the quality-of-service requirements of the receivers. We develop a two-layer, penalty-based block coordinate descent algorithm to solve this challenging non-convex optimization problem and employ manifold optimization to update the analog precoding weights and IRS phase shifts. We also derive a low-complexity, decoupled iterative design where the analog precoder is updated via the stochastic gradient descent algorithm and the PB is computed via the successive convex approximation method. Numerical simulations highlight the performance gains of the proposed schemes over various benchmarks and shed light on the impact of the parameter settings on the performance.